2021
DOI: 10.1093/humrep/deaa366
|View full text |Cite
|
Sign up to set email alerts
|

Disruption and recovery of testicular function during and after androgen abuse: the HAARLEM study

Abstract: STUDY QUESTION What is the speed and extent by which endogenous testosterone production and spermatogenesis recover after androgen abuse? SUMMARY ANSWER Testosterone concentrations normalized within 3 months after discontinuation of androgen abuse in most subjects but recovery of spermatogenesis took longer—approximately 1 year. WHAT IS KNOWN ALREADY An estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 19 publications
0
42
0
Order By: Relevance
“…The problems related to ongoing AAS use include both physical and mental health issues such as gynecomastia, cardiovascular and liver pathology, mood swings, irritability, and aggressiveness (Horwitz et al, 2019;Piacentino et al, 2015). Withdrawal symptoms related to hypogonadism are commonly experienced for months during off periods (Smit et al, 2021), contributing to continued AAS use to relieve these symptoms. The most central symptoms to the network indicate that this cycle of experiencing side effects and potentially continuing AAS use to alleviate these side effects typifies AAS dependence.…”
Section: Discussionmentioning
confidence: 99%
“…The problems related to ongoing AAS use include both physical and mental health issues such as gynecomastia, cardiovascular and liver pathology, mood swings, irritability, and aggressiveness (Horwitz et al, 2019;Piacentino et al, 2015). Withdrawal symptoms related to hypogonadism are commonly experienced for months during off periods (Smit et al, 2021), contributing to continued AAS use to relieve these symptoms. The most central symptoms to the network indicate that this cycle of experiencing side effects and potentially continuing AAS use to alleviate these side effects typifies AAS dependence.…”
Section: Discussionmentioning
confidence: 99%
“…While the potential benefits of various substances have been identified in small scale studies (Anawalt, 2019;Tan & Scally, 2009) and supported by anecdotal evidence (Griffiths, Henshaw, McKay, & Dunn, 2016;Llewellyn, 2017), there has been little research conducted in relation to PCT. In fact, in direct contradiction regarding the benefits of PCT and suggestions from a recent study of 80 users of PCT concluded that, there was hardly any evidence to support its use, that tamoxifen had negligible effects on the actions of AAS and that hCG had no detectable effect on testicular size or spermatogenesis (Smit, Buijs, de Hon, den Heijer, & de Ronde, 2021). Caution is required in the interpretation of research with relatively small sample sizes and the use of illicitly obtained medications with a lack of data on drug provenance however this illustrates the lack of progress in relation to answering a key question regarding AAS and a tenet of any harm reduction activity.…”
Section: Effective Responsesmentioning
confidence: 94%
“…Measurements took place before, during and twice after the cycle. Health effects were divided into several categories: positive and negative adverse effects reported by the subjects, the results of kidney and liver biochemistry in blood, and the outcome of psychological questionnaires [4 ▪ ]; the disruption and recovery of endogenous testosterone production and spermatogenesis [5 ▪ ]; the change of cardiovascular parameters during androgen abuse, such as blood pressure, lipid metabolism and erythrocytosis [6 ▪ ]; and change of cardiac structure and function as evaluated with 3D echocardiography [7].…”
Section: Description Of Studiesmentioning
confidence: 99%
“…In the last 2−3 years several publications reported data from the HAARLEM study [3,4 ▪ –6 ▪ ,7], which is an acronym for health risks of anabolic androgenic steroid use by male amateur athletes. This cohort study takes precedence over much of the existing literature in this field due to its prospective design and relatively large size.…”
Section: Introductionmentioning
confidence: 99%